Reflections on Cross-Curricular and Digital Competency Training in Higher Education Institutions of Mexico - Vega Cadena, Uzziel Japhet (2017)
Education in the 21st century faces the great challenge of training professionals who can meet contemporary labor needs in a globalized and highly-skilled environment. Therefore, it is required that Higher Education foster the development of work and digital skills that allow cross-cutting and interrelated projects to be developed so that the student has the necessary tools to deal with changes in the knowledge society in a competitive way. Therefore, the aim of this essay is to reflect on the role of higher education in Mexico in the so called “knowledge society” and contribute to the analysis of the relationship between educational institutions with the government, society, and productive sector. To this end, in a first section current Mexico’s educational policies are described; in a second section, a theoretical approach to the definition of competencies or skills is made to finally review the importance of Digital Skills in the current age; finally, the conclusions are presented.